Pengobatan dengan Benda Haram Perspektif Ulama Mazhab: Treatment with Haram Object from the Perspective of the Mazhab Scholars - Muhammad Nirwan Idris; Kurnaemi Anita; Muhammad Anugrah (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
This research aims to find out and understand the legal concept of using haram objects in treatment from the perspective of sectarian scholars. This research is a descriptive qualitative research based on literature (Library research) which is based on relevant texts as an analytical tool, using normative and comparative approach methods. The research results first discuss the emergency limitations of the fuqaha perspective. Furthermore, the results of the study found that: 1) Ulama agrees on the prohibition of seeking treatment with haram objects under normal circumstances without any element of emergency. It's just that they have different opinions in emergencies, some of which absolutely prohibit it, consisting of the majority of Hanafiyah, Malikiyah, Syafi'iyah and Hanabilah scholars. Some Hanafiyah scholars allow it with conditions; 2) The opinion chosen in this matter is permissible with conditions, namely that there is an element of emergency and a recommendation from a trusted Muslim doctor, where it is confirmed that the drug can treat the disease and there is no halal drug that can replace it.